Problems And Prospects of Land Use of The Agricultural Sector of Ukraine - KOLOTUKHA Serge; GVOZDEJ Nataliia; CHVERTKO Liudmyla; KORNIIENKO Tetiana; VINNYTSKA Oksana; PTASHNYK Svitlana (Communications of International Proceedings, 2021)
Land relations have always been the focus of the public, different segments of the population, regardless of the presence or absence of land. In modern conditions, the relevance of these relations has increased significantly. The situation in land relations and the system of land use in rural areas remains complex and unresolved. The current state of land use does not fully meet the requirements of rational use of natural resources. This is confirmed by the fact that as a result of intensive land use the ecologically safe balance of land area is disturbed, the negative environmental consequences of man-made impact are felt, which cause significant damage to land resources, human health, cause significant economic damage to the economy. Thus, given the unsatisfactory use of land resources, the problem of rational use and protection of land in the modern period is of particular importance, and its solution requires effective measures of influence, including legal.
Keywords: Agricultural Sector; Financial Resources; Financing; Land; Agriculture; Price; Investment.